Edukasi Persiapan Pernikahan Bahagia selama Pandemi Covid-19 : Perspektif Agama dan Kesehatan - Nadhiroh, Aim Matun; Rozifah, Annisa Wigati; Rosyid, Abdur (Batara Wisnu : Indonesian Journal of Community Services, 2021)
Economic problems are often one of the causes of the increasing divorce rate. With the pandemic and the increasing number of cases of COVID-19 sufferers, both at the national and regional levels, this may also have an impact on the addition of divorce cases, although it is not the main factor due to the pandemic. Before the pandemic, the divorce rate in Bangkalan continued to increase every year. Many factors cause the increasing number of divorce cases. The most important activity is to provide education about marriage preparation both from a health and religious perspective with the hope that everyone who decides to get married will understand more about the responsibilities of the role that will be carried out and the marriage is happy in the hereafter